The Influence of Digital Marketing, Social Media, Promotion and Influencers on Purchasing Decisions for Iphone Products - Akbar, Mohamad; Wijaya, Ermy; Astuty, Kamelia (Research Parks Publishers, 2024)
The aim of this research is to determine the influence of digital marketing, social media, promotion and influencers on purchasing decisions for iPhone products. The data collection method in this research uses questionnaire techniques, with a sample of 130 respondents.The results of the research show that multiple linear regression Y = 0.445 + 0.008 X1 + 0.293 X2 + 0.413 X3 + 0.276 , promotion (X3) and Influencer value is 0 (zero), then the purchase decision (Y) value for iPhone products is 0.115. The results of the research show that the digital marketing test (XI) shows tcount 2.003 > ttable 1.656 and significance 0.018 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning digital marketing has a positive and significant effect on purchasing decisions for iPhone products. The results of the social media test (X2) show tcount 2.077> ttable 1.656 and significance 0.040 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that social media has a positive and significant effect on the decision to purchase iPhone products. The results of the promotion test (X3) show tcount 4.854> ttable 1.656 and significance 0.000 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning promotion has a positive and significant effect on the decision to purchase iPhone products. The results of the influencer test (X4) show tcount 1.971> ttable 1.656 and significance 0.041 <0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that influencers have a positive and significant influence on the decision to purchase iPhone products. As a result of comparing the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 11.7515 > 2.44, so it is concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between digital marketing (XI), social media (X2), promotion (X3) and influencers. (X4) on the decision to purchase iPhone products. This can be seen at the significance level of 0.000 <0.05. This can be seen at the significance level of 0.000 <0.05.